2019
DOI: 10.3390/ijms20246109
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Derived Extracellular Vesicle-Associated MicroRNAs in Intercellular Communication: One Cell’s Trash Is Another Cell’s Treasure

Abstract: Several non-protein-coding genomic regions, previously marked as “junk DNA”, have been reported to be transcriptionally active, giving rise to non-coding RNA species implicated in fundamental biological and pathological processes. In particular, microRNAs (miRNAs), a class of small non-coding RNAs mediating post-transcriptional gene silencing, are causally involved in several human diseases, including various cancer types. Extracellular vesicles (EVs) are membranous structures physiologically released by most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 203 publications
(226 reference statements)
0
50
0
Order By: Relevance
“…Moreover, it was widely demonstrated that the cargo of Extracellular Vesicles (EVs), of which exosomes are the most studied, are enriched with miRNAs which play crucial roles in cancer diagnostics, prognosis and also therapeutic approaches [321,322]. Although clinical application of EV-associated miRNAs is still in its infancy, several studies have demonstrated their potential role in preclinical cancer models [321]. For example, the exomiRNA cytotoxic signal delivered from NK to tumor cells was shown to reduce tumor growth [321].…”
Section: Delivery Strategies Of Mirna-associated Therapeuticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, it was widely demonstrated that the cargo of Extracellular Vesicles (EVs), of which exosomes are the most studied, are enriched with miRNAs which play crucial roles in cancer diagnostics, prognosis and also therapeutic approaches [321,322]. Although clinical application of EV-associated miRNAs is still in its infancy, several studies have demonstrated their potential role in preclinical cancer models [321]. For example, the exomiRNA cytotoxic signal delivered from NK to tumor cells was shown to reduce tumor growth [321].…”
Section: Delivery Strategies Of Mirna-associated Therapeuticsmentioning
confidence: 99%
“…Although clinical application of EV-associated miRNAs is still in its infancy, several studies have demonstrated their potential role in preclinical cancer models [321]. For example, the exomiRNA cytotoxic signal delivered from NK to tumor cells was shown to reduce tumor growth [321]. Recently, Neviani et al showed that NK-mediated killing of neuroblastoma cells is, at least partly, mediated by the transfer of miR-186 in EVs [321,323].…”
Section: Delivery Strategies Of Mirna-associated Therapeuticsmentioning
confidence: 99%
See 3 more Smart Citations